ANALYSIS OF THE CONCEPT OF STRATEGIC MANAGEMENT AND QUALITY OF MADRASAH ALIYAH - Umar, Yusuf (Journal of Islamicate Studies, 2018)
This article analyzes the concept of strategy management and quality in Madrasah Aliyah. As one of the educational institutions, Madrasah Aliyah really need their own management pattern, especially towards quality education. Philosophically Management in the context of the Madrasah Aliyah underlies a leadership in order to be able to build the life of the Madrasah Aliyah organization by developing a culture called the values ​​of excellence in Islamic teachings. The management organization in the Madrasah Aliyah requires a leader and manager who understand the basic concepts of strategic management and the quality of the Madrasah Aliyah so that the manager has a wise vision and is able to inspire staff / workers and all the community organizations of the Aliyah madrasah. Using the literature survey method, this article reveals that management strategies and quality of the Madrasah Aliyah are specifically useful for determining ways and strategies, so that an organization can be managed effectively and efficiently. With an independent management pattern, it can be found the right way to manage resources, the easiest way to do the work, the cheapest funds to finance work, the shortest time to do the work, the right tools to lighten the burden and shorten the distance to carry out work, and produce quality and quality according to the vision, mission, and goals of Madrasah Aliyah.